Intrapreneurship or entrepreneurship? - Simon C. Parker (Institute for the Study of Labor (IZA), 2009)
I explore the factors that determine whether new business opportunities are exploited by starting a new venture for an employer ('nascent intrapreneurship') or independently ('nascent entrepreneurship'). Analysis of a nationally representative sample of American adults gathered in 2005-06 uncovers systematic differences between the drivers of nascent entrepreneurship and nascent intrapreneurship. Nascent entrepreneurs tend to leverage their general human capital and social ties to organize ventures which sell directly to customers, whereas intrapreneurs disproportionately commercialize unique new opportunities which sell to other businesses. Implications of the findings are discussed.
urn:nbn:de:101:1-20090615104
Keywords: L26; M13; 330; Nascent entrepreneurship; intrapreneurship; sample selection; Intrapreneuring; Unternehmer; Innovation; Humankapital; Social Capital; USA